Altered bodily self‐consciousness in multiple sclerosis. Issue 3 (10th September 2017) - Nava, Elena; Mattioli, Flavia; Gamberini, Chiara; Stampatori, Chiara; Bellomi, Fabio; Turati, Chiara; Capra, Ruggero; Bolognini, Nadia
Abstract : In this study, we assessed the impact of multiple sclerosis (MS) on bodily self‐consciousness (BSC) using the Rubber Hand Illusion. Patients with MS showed a dissociation between body ownership and self‐location: they did report an explicit ownership of the rubber hand, but they did not point towards it, showing a defective ability of localizing body parts in space. This evidence indicates that MS may affect selective components of BSC, whose impairment may contribute to, and even worsen, the functional disability of MS.